1993
DOI: 10.1144/gsl.qjeg.1993.026.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical evaluation of untreated and cement-treated Ajali Sandstone from southeastern Nigeria

Abstract: The grain size analysis and the Atterberg limit values indicate that the Ajali Sandstone falls into the A-3 and SP-SW classes of the AASHTO and the Unified Soil Classification systems respectively. The low values of the coefficient of uniformity 2.9-3.4 show the deposit is uniformly graded and the soil is deficient in silt-clay fractions. At the optimum moisture content of 8% the untreated soil has a maximum dry density of 1.77 Mg/m3. The CBR of the soil when compacted to the standard Proctor optimum and soake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However high strength reduction of about 40% was noted when the stabilized mixture was soaked in water even with as much as 10% cement, thus suggested the protection of the pavement from water ingress. [5] Noted that there was significant improvement in the shear strength when 8% cement was used to stabilize the Ajali sandstone soils: soaked CBR value in excess of 100% was obtained.…”
Section: Use Of Cement Stabilization In Thementioning
confidence: 99%
“…However high strength reduction of about 40% was noted when the stabilized mixture was soaked in water even with as much as 10% cement, thus suggested the protection of the pavement from water ingress. [5] Noted that there was significant improvement in the shear strength when 8% cement was used to stabilize the Ajali sandstone soils: soaked CBR value in excess of 100% was obtained.…”
Section: Use Of Cement Stabilization In Thementioning
confidence: 99%
“…Strength improvements of the studied sabkha soil of as much as ten times have been obtained using lime or cement contents as low as 5%, and improvements in strength of about 20 times have been achieved within only seven days of curing. If, according to Eze & Suoware (1993), acceptable materials for use as road and airfield bases are usually required to have a minimum unconfined compressive strength of 1400kPa after 7 days, then only the 10% lime-and cement-sabkha mixtures could be considered to be suitable. However, if a longer curing period were to be allowed then it may be possible for the lime and cement contents to be reduced to below 10%.…”
Section: Effect Of Water:binder Ratio On Strengthmentioning
confidence: 99%
“…The author then suggested that pavement constructed with the composite must be protected from water. [5] reported effect of cement on sandstone soils which consist of fine to medium sand fraction, 5 -7% silt, and average clay content of 50%. Significant improvement in the density, shear strength, and soaked CBR (value up to 100%) were noted, when about 8% cement was used to stabilise soils.…”
Section: Introductionmentioning
confidence: 99%